Learning 3DS Max 2012 - Mennenoh, Brian (InfiniteSkills, 2011)
"In this video tutorial on Learning 3DS Max 2012, expert author and animator Brian Mennenoh introduces you to the many features of this 3D modeling and animation software from AutoDesk. Brian has over 20 years experience working with 3D, and his engaging teaching style draws you in and allows you to enjoy the sometimes complex intricacies of such a powerful software program. Using a single project throughout the whole training course, you will learn how to use the interface and a good production workflow, several modeling techniques, material creation, basic lighting, camera setups, matching a camera to a background image, rendering settings and more. At the end of the lessons you will have created a robot and a fully skinned fairy, rigged with bones, battling with crayons after their kids walked away from a coloring project. By the completion of this computer based training course, you will have a solid foundation in 3ds Max and be able to start working on your own projects, building on the knowledge gained throughout the lessons. Extensive working files are included to allow you to work alongside the author in this project, learning with the same files that he is using in the training."--Resource description page.